Penguatan Numerasi Murid Melalui Implementasi Media Obibul Pada Pembelajaran Bilangan Bulat SMP - Diva Ummi Kalsum Wijaya; Siti Rahma; Nurhalisa Nurhalisa; Sanrawati Sanrawati; Nurhidaya Nurhidaya; Aprisal Aprisal; Nursafitri Amin; Ana Muliana M (Educational Consultant & Counseling Career (EC3) Mataram, 2026)
Integer operations constitute a fundamental topic in mathematics that students must master, as they serve as the basis for understanding more advanced mathematical concepts. However, preliminary observations and interviews with mathematics teachers of Grade VII students at SMP Negeri 9 Majene revealed that many students still experience difficulties in understanding integer operations, particularly those involving positive and negative signs in multi-step calculations. This community engagement program was designed to enhance students’ conceptual understanding of integer operations through the use of the Integer Operation Board (OBIBUL) as an instructional medium. The program was implemented in a Grade VII classroom at SMP Negeri 9 Majene and consisted of three stages: preparation, implementation, and evaluation. The implementation phase included material demonstrations, guided practice using the OBIBUL media, group quizzes, and evaluation through questionnaires. The findings indicate that the OBIBUL board effectively facilitated students’ understanding of integer operations by providing concrete visual representations through number lines and directional operation arrows, enabling abstract concepts to become more accessible and meaningful. Furthermore, the use of the media encouraged greater student participation and engagement during the learning process. Both students and teachers also expressed positive responses toward the implementation of the OBIBUL board, describing it as interactive, engaging, and supportive of conceptual learning. Therefore, the OBIBUL board may serve as an effective alternative instructional medium for improving junior high school students’ understanding of integer operations in mathematics learning.